Learning about friendship : stories to support social skills training in children with Asperger syndrome and high functioning autism - Al-Ghani, K. I.; Al-Ghani, Haitham (London : Jessica Kingsley Publishers, 2011)
Making friends can be a challenge for all children, but those with autistic spectrum disorder (ASD) can struggle more than most. This collection of ten fully-illustrated stories explores friendship issues encountered by children with ASD aged four to eight and looks at how they can be overcome successfully.
Includes bibliographical references.
Keywords: Asperger's syndrome in children -- Patients -- Rehabilitation; Asperger's syndrome in children -- Patients -- Education; Asperger's syndrome in children -- Social aspects; Social skills in children -- Study and teaching